2019
DOI: 10.3892/ol.2019.10227
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers for the diagnosis of cervical cancer by quantitative label‑free mass spectrometry analysis

Abstract: Due to the invasive procedure associated with Pap smears for diagnosing cervical cancer and the conservative culture of developing countries, identifying less invasive biomarkers is of great interest. Quantitative label-free mass spectrometry was performed to identify potential biomarkers in the urine samples of patients with cervical cancer. This technique was used to study the differential expression of urinary proteomes between normal individuals and cancer patients. The alterations in the levels of urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…MMRN1 has 2 isoforms, each measuring 138 and 58 kDa, due to alternative splicing. Isoform-1 of MMRN-1 has been identified as a potential serum biomarker for multiple myeloma and lung cancer (49) and urinary biomarker for cervical cancer (57). In the present study, serum levels of isoform-2 of MMRN-1, as confirmed by mass spectrometry, were decreased in the serum of HPV positive normal controls and in patients with early and late stage cervical cancer.…”
Section: Discussionsupporting
confidence: 63%
“…MMRN1 has 2 isoforms, each measuring 138 and 58 kDa, due to alternative splicing. Isoform-1 of MMRN-1 has been identified as a potential serum biomarker for multiple myeloma and lung cancer (49) and urinary biomarker for cervical cancer (57). In the present study, serum levels of isoform-2 of MMRN-1, as confirmed by mass spectrometry, were decreased in the serum of HPV positive normal controls and in patients with early and late stage cervical cancer.…”
Section: Discussionsupporting
confidence: 63%
“…Ras-related protein Rab-6A was also listed as an unfavourable biomarker for endometrial, liver and pancreatic cancers, Ubiquitin-40S ribosomal protein S27a as unfavourable biomarker for renal and liver cancer, and Tripartite motif-containing protein 29 as an unfavourable biomarker for endometrial, stomach and pancreatic cancer. Previous studies have reported Ubiquitin-40S ribosomal protein S27a as being present in higher amounts in the urine of cervical cancer patients compared to controls when measured with mass spectrometry [ 28 ] and an overexpression of Tripartite motif-containing protein 29 (both mRNA and protein) in cervical cancer tissue compared to matched adjacent cervical tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In-solution tryptic-digestion was performed as described previously with certain modifications ( 23 ). Briefly, 10 µg protein from fibroblast lysates (pooled healthy controls and individual patient samples) was reduced in 10 mM DTT for 5 min at 95˚C and alkylated with 1/10 volume of 20 mM iodoacetamide, prior to incubation for 30 min in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A nanoACQUITY UPLC system (Waters Corporation) coupled with an amaZon speed Ion Trap mass spectrometer (Bruker Corporation) was used to identify peptides/proteins, as described previously ( 23 ). The tryptic-digested peptides were dissolved in 0.1% formic acid in H 2 O and injected into a nanoACQUITY UPLC column (1.7 µm BEH, 75 µm x 200 mm C 18 , Water Corporation) at a flow rate of 300 nl/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation